Crystallization and X-ray structure analysis of a thermostable penicillin G acylase from alcaligenes faecalis - Varshney, Nishant Kumar; Kumar, R. Suresh; Ignatova, Zoya; Prabhune, Asmita; Pundle, Archana; Dodson, Eleanor J.; Suresh, C. G. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2012)
{The enzyme penicillin G acylase (EC 3.5.1.11) catalyzes amide-bond cleavage in benzylpenicillin (penicillin G) to yield 6-aminopenicillanic acid, an intermediate chemical used in the production of semisynthetic penicillins. A thermostable penicillin G acylase from Alcaligenes faecalis (AfPGA) has been crystallized using the hanging-drop vapour-diffusion method in two different space groups: C2221, with unit-cell parameters a = 72.9
Keywords: calcium binding; disulfide bridges; Ntn hydrolases; orthorhombic form; tetragonal form; Thermostability